A Clinical Study on Secondary Breast Cancer after Treatment for Hodgkin’s Disease - Belhajjam, Loubna; Alami, Zineb; Kouadir, Asmaa; Elmazghi , Abderahmane; Bouhafa, Touria; Hassouni, Khalid (Research Highlights in Disease and Health Research Vol. 5, 2023)
Improved survival of patients treated for Hodgkin's disease has been increased at the cost of late complications, the most common of which are secondary neoplasias including breast cancers, which make up 6–9% of these neoplasias after treatment for MDH. Survivors of Hodgkin's disease may have a long life expectancy nowadays, and it is crucial to develop appropriate methods for estimating the risk of late breast cancer. Young age and radiotherapy are mainly the most advantageous factors. In this report, we describe the observation of a patient who was treated for Hodgkin's disease at the age of 17. After 17 years, she was diagnosed with triple-negative right breast cancer and received adjuvant chemotherapy and radiotherapy as well as breast-conserving surgery. We provide an overview of the risk factors, diagnostic, prognostic, and therapeutic options that are modified by the Hodgkin's disease treatment received for these secondary mammary cancers.